P10.09 View on human papillomavirus vaccination among at-risk men in wuxi, china: a cross-sectional study. (13th September 2015) - Meng, XJ; Zou, HC
Abstract : Introduction: Human papillomavirus (HPV) infection is common among sexually active men who have sex with men (MSM) and men who have sex with women (MSW). The quadrivalent HPV vaccine is effective in preventing HPV infection and HPV related morbidities in both MSM and MSW. View on HPV vaccination among MSM and MSW in China has not been studied. Methods: We enrolled MSM from the community and MSW from a sexual health clinic in Wuxi, China. A questionnaire about participants' socio-demographic characteristics and view on HPV vaccination was collected. Results: A number of 186 MSM and 182 MSW were recruited. The proportions of having ever heard of HPV among these two groups were 18.4% and 23.1%, respectively. The proportions of having ever heard of HPV vaccine were 10.2% and 15.4%, respectively. MSW (70.9%) were significantly more willing to take HPV vaccine than MSM (34.9%) (p < 0.001). Only 26.2% of MSM and 20.2% of MSW were willing to take free HPV vaccine before the age of 20 when they commenced their sexual behaviours. MSM preferred receptive anal sex (OR: 3.8, 95% CI: 1.7–13.5), never using condom in anal sex in the past 6 months (OR: 3.4, 95% CI: 1.4–20.1), ever diagnosed with STIs (OR: 3.3, 95% CI: 1.2–8.3) and ever receiving HIV/AIDS related service (OR: 1.6, 95% CI: 1.1–4.3) and MSW having female commercial sex (OR: 1.7, 95% CI: 1.2–8.5), never using condom in commercial sex (OR: 1.9, 95% CI: 1.3–8.5) and diagnosis of an STI (OR: 2.0, 95% CI: 1.6–7.2) were more likely to accept free HPV vaccine. Conclusion: Sexually active MSM and MSW in China lacked knowledge of HPV. The majority of homosexual men would not benefit from HPV vaccination as their sexual debut proceeds vaccine uptake. Aggressive education aimed at increasing knowledge of HPV and HPV vaccination among these men is warranted. Disclosure of interest statement: All authors declare no competing interests.